EFEKTIVITAS PEMANFAATAN PROBIOTIK PADA BUDIDAYA IKAN LELE DUMBO (CLARIAS GARIEPINUS) SISTEM BIOFLOK: The Fffectivity Of Probiotic Toward African Catfish (Clarias gariepinus) Culture In Biofloc System - Putra H., Moh. Syahdan; Liliyanti, Mita Ayu; Kalih, L.A.T.T.W. Sukmaring; Soraya, Indah (Al-Qalbu: Jurnal Pendidikan, Sosial dan Sains, 2024)
This study aims to investigate the effect of using different probiotics on growth, survival rate, and feed conversion rate of African catfish on the biofloc system. The study was conducted at the SMK PP Negeri Mataram Laboratory from August to September 2020. The research design used a completely randomized design (CRD) with 4 treatments with 3 replications. Data collection was carried out by measuring fish length and fish weight. The data analyzed were daily weight growth rate, daily length growth rate, specific growth rate, survival rate, feed conversion rate, growth pattern, and condition factors. Growth rates, survival and feed conversion rates were analyzed using the ANOVA method and LSD test. The results indicated that the growth rate of daily weight, length growth rate, specific growth rate, and conversion rate has optimal in the treatment of Bacillus + Lactobacillus probiotic. In this treatment, the average daily weight growth rate in the treatment was 0.13 gr/day, the daily length growth rate for African catfish was 0.130 cm/day, the specific growth rate was 1.76%/day, and the average feed conversion rate of 0.641. The highest survival rate also occurred in the treatment of Bacillus + Lactobacillus probiotics with an average of 81.33%. The growth pattern of African catfish with the biofloc system is negative allometric, the coefficient value (b) is less than 3. The condition factor for African catfish is categorized as flat.